Core circadian clock gene expression in human dental pulp‐derived cells in response to L‐mimosine, hypoxia and echinomycin. (13th July 2018) - Janjić, Klara; Kurzmann, Christoph; Moritz, Andreas; Agis, Hermann
Abstract : Core circadian clock genes set the pace for a wide range of physiological functions, including regeneration. The role of these genes and their regulation in the dental pulp, in particular under hypoxic conditions, is unknown. Here we investigated if core clock genes are expressed in human dental pulp‐derived cells (DPC) and if their expression is modulated by the hypoxia mimetic agent, L‐mimosine (L‐MIM), hypoxia or echinomycin. Dental pulp‐derived cells in monolayers and spheroids were treated with L‐MIM, hypoxia or echinomycin. mRNA levels of the core circadian clock genes were analysed using quantitative PCR (qPCR) and their protein levels were analysed by western blot. All core clock genes and proteins were produced in DPC monolayer and spheroid cultures. The expression of cryptochrome circadian regulators and period circadian regulators was reduced by L‐MIM, hypoxia and echinomycin at mRNA, but not at protein levels. Time course experiments indicated that modulations were based on alterations in overall mRNA levels of core circadian clock genes. Our results suggest a potential role of the core circadian clock in the response of dental pulp to hypoxia. Future studies need to consider that regulation of the core circadian clock at mRNA levels might not be paralleled by modulation of protein levels.